2016
DOI: 10.1037/tra0000027
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of overgeneral memory: The role of trauma history, mood, and the presence of posttraumatic stress disorder.

Abstract: A number of studies suggest that a history of trauma, depression, and posttraumatic stress disorder (PTSD) are associated with autobiographical memory deficits, notably overgeneral memory (OGM). However, whether there are any group differences in the nature and magnitude of OGM has not been evaluated. Thus, a meta-analysis was conducted to quantify group differences in OGM. The effect sizes were pooled from studies examining the effect on OGM from a history of trauma (e.g., childhood sexual abuse), and the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
102
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 63 publications
12
102
4
Order By: Relevance
“…These findings apply to people with depressive symptoms or clinical depression (Van Vreeswijk & de Wilde, 2004;Williams, 1996), also in later life (Serrano, Latorre, & Gatz, 2007). A recent meta-analysis shows that overgeneralization in depression is particularly found with regard to positive memories (Ono, Devilly, & Shum, 2016). This finding matches earlier research on mood congruence effects that has shown that people in depressed mood recall fewer positive memories (Bower, 1981;Miranda & Kihlstrom, 2005;Singer & Salovey, 1988).…”
supporting
confidence: 79%
“…These findings apply to people with depressive symptoms or clinical depression (Van Vreeswijk & de Wilde, 2004;Williams, 1996), also in later life (Serrano, Latorre, & Gatz, 2007). A recent meta-analysis shows that overgeneralization in depression is particularly found with regard to positive memories (Ono, Devilly, & Shum, 2016). This finding matches earlier research on mood congruence effects that has shown that people in depressed mood recall fewer positive memories (Bower, 1981;Miranda & Kihlstrom, 2005;Singer & Salovey, 1988).…”
supporting
confidence: 79%
“…Prior work suggests that activity in the PCC and hippocampus is associated with successful retrieval of autobiographical events (56, 58, 59), and notably, that the functional connectivity between the PCC and hippocampus is involved in episodic autobiographical remembering (60, 61). Individuals with PTSD tend to retrieve overgeneral autobiographical memories, i.e., generic memories that are devoid of specific details (62–64). This tendency to retrieve overgeneral memories may be associated with alterations in a PCC-hippocampal pathway that is important for retrieving details of autobiographical memories.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with major depressive disorder display mood-congruent memory effects, in that they are more likely to recall negatively- than positively-valenced information (Matt, VĂĄzquez, & Campbell, 1992). Individuals with PTSD may be similarly impaired at accurate self-report, due to a tendency to overgeneralize autobiographical memories (e.g., Moradi, Abdi, Fathi-Ashtiani, Dalgleish, & Jobson, 2012; Ono, Devilly, & Shum, 2015 May 11 [Epub ahead of print]); in fact, a recently-defined subtype of PTSD involves dissociative symptoms, including disruptions in memory, identity, and perceptions (Bennett, Modrowski, Kerig, & Chaplo, 2015 May 25 [Epub ahead of print]; Tsai, Armour, Southwick, & Pietrzak, 2015). Finally, the form factor of a paper-and-pencil questionnaire may not be ideal for use with populations that have limited attention span or poor vocabulary and/or literacy skills.…”
Section: Introductionmentioning
confidence: 99%